Φ-Admissible Sublinear Singular Operators and Generalized Orlicz-Morrey Spaces - Javanshir J. Hasanov (Journal of Function Spaces)
We study the boundedness of Φ-admissible sublinear singular operators on Orlicz-Morrey spaces MΦ,φℝn. These conditions are satisfied by most of the operators in harmonic analysis, such as the Hardy-Littlewood maximal operator and Calderón-Zygmund singular integral operator.